The Effect of Logotherapy Oriented Group Counseling on Post-Traumatic Embitterment Disorder - Betül Düşünceli; Mustafa Koç (Sakarya University Journal of Education)
The basic aim of this study is to examine effect of logotherapy oriented group counseling application on post-traumatic embitterment disorder. The study was carried out by experimental design because it is aimed to determine cause-effect relationship between independent variable (Logotherapy oriented group counseling) and dependent variable (Post-Traumatic Embitterment Disorder). The design of the study is the pretest-posttest control group design from true experimental designs. Participants are 22 university students whose post-traumatic embitterment disorder symptoms levels were high. It is randomly assigned that which participant will be in the experimental or control group. Each group was formed from 11 university students. Data had been collected by Post-Traumatic Embitterment Disorder Scale. While experimental group was applied Logotherapy oriented group counseling for ten weeks, any treatment program applied to control group. The same scale was applied three times for pre-experimental, post-experimental, and follow up processes. Data were analyzed by SPSS package program. According to findings of the research, Logotherapy oriented group counseling has effect on reducing the post-traumatic embitterment disorder symptoms. Findings were discussed by associating with the related literature and suggestions were made in consideration of findings.